2014
DOI: 10.1016/j.rse.2014.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Global-scale evaluation of two satellite-based passive microwave soil moisture datasets (SMOS and AMSR-E) with respect to Land Data Assimilation System estimates

Abstract: International audienceGlobal Level-3 surface soil moisture (SM) maps derived from the passive microwave SMOS (Soil Moisture and Ocean Salinity) observations at L-band have recently been released. In this study, a comparative analysis of this Level 3 product (referred to as SMOSL3) along with another Surface SM (SSM) product derived from the observations of the Advanced Microwave Scanning Radiometer (AMSR-E) at C-band is presented (this latter product is referred to as AMSRM). SM-DAS-2, a SSM product produced b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
145
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(154 citation statements)
references
References 83 publications
9
145
0
Order By: Relevance
“…Conversely, both SMAP L4 SM and AMSR2 L3 SM exhibited weak correlations with the reference data in dry regions (e.g., for the Shrub/Scrub land cover type in the western region) (Figures 7 and 9), since that region is mainly desert with low vegetation cover (Figures 13 and 14). These results could be related to the low range of variation in soil moisture in these regions, which roughly corresponds to the expected retrieval accuracy of the remotely sensed products [22]. Meanwhile, both SMAP L4 SM and AMSR2 L3 SM also exhibited weak correlations with the reference data and large TC estimate error in evergreen forest regions.…”
Section: Discussionsupporting
confidence: 52%
“…Conversely, both SMAP L4 SM and AMSR2 L3 SM exhibited weak correlations with the reference data in dry regions (e.g., for the Shrub/Scrub land cover type in the western region) (Figures 7 and 9), since that region is mainly desert with low vegetation cover (Figures 13 and 14). These results could be related to the low range of variation in soil moisture in these regions, which roughly corresponds to the expected retrieval accuracy of the remotely sensed products [22]. Meanwhile, both SMAP L4 SM and AMSR2 L3 SM also exhibited weak correlations with the reference data and large TC estimate error in evergreen forest regions.…”
Section: Discussionsupporting
confidence: 52%
“…For a consistent and fair comparison, in our study we use the nearest interpolation method to resample the SMAP passive, the SMOS, and the FY3B soil moisture products to a spatial resolution of 0.25 • , the same as that of JAXA or LPRM AMSR2 and ESA CCI, as well as to resample the SMAP enhanced passive soil moisture to a spatial resolution of 0.1 • , the same as that of JAXA AMSR2. The same method has been applied in many comparison studies of soil moisture products [16,22,57,58]. The blue grid at a 0.1 • resolution and the red grid at a 0.25 • resolution, shown in Figure 1, were selected as the validation grids in this study, since they contain the most stations in the two network regions.…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated soil moisture estimation from space using passive microwave (e.g., [2][3][4][5]) and active microwave (scatterometer) (e.g., [4,6,7]) at a coarse (25-150 km) spatial resolution. On the other hand, active microwave SAR data have been successfully used to retrieve the soil moisture at a finer (less than 100 m) spatial resolution but with a coarse (approximately 3 weeks) temporal resolution [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…SMOS provides soil moisture at a temporal resolution of 3 days at the equator and at a nominal spatial resolution of 40 km [26]. Several validation studies provided insights into the reliability and robustness of the soil moisture estimates from SMOS [2,[27][28][29] and over India [30]. RADAR SATellite-2 (RADARSAT-2) is an active microwave satellite mission operating in C-band, capable of retrieving surface soil moisture at a spatial resolution of less than 100 m and with a temporal resolution of 24 days [31].…”
Section: Introductionmentioning
confidence: 99%